The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10295-008-0427-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of new isolated Ralstonia eutropha strain A-04 and kinetic study of biodegradable copolyester poly(3-hydroxybutyrate-co-4-hydroxybutyrate) production

Abstract: A new isolated bacterial strain A-04 capable of producing high content of polyhydroxyalkanoates (PHAs) was morphologically and taxonomically identified based on biochemical tests and 16S rRNA gene analysis. The isolate is a member of the genus Ralstonia and close to Ralstonia eutropha. Hence, this study has led to the finding of a new and unexplored R. eutropha strain A-04 capable of producing PHAs with reasonable yield. The kinetic study of poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)] producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 21 publications
2
48
0
2
Order By: Relevance
“…The 1 H NMR spectra showed that the polymers are composed of two monomer units, 3HB and 4HB, and the spectrum signals ( Fig. 1) appear identical to those obtained for P(3HB-co-4HB) by other authors [19,25]. The fraction of each monomer was calculated from the areas of the 4.11 ppm signal from 4HB and the 5.26 ppm signal from 3HB (C and B in Fig.1 ), bearing in mind that the 4HB and the 3HB signals correspond, respectively to two and one hydrogen atoms.…”
Section: Evidence Of 4hb Incorporation In the Polymer By 1 H Nmrsupporting
confidence: 58%
“…The 1 H NMR spectra showed that the polymers are composed of two monomer units, 3HB and 4HB, and the spectrum signals ( Fig. 1) appear identical to those obtained for P(3HB-co-4HB) by other authors [19,25]. The fraction of each monomer was calculated from the areas of the 4.11 ppm signal from 4HB and the 5.26 ppm signal from 3HB (C and B in Fig.1 ), bearing in mind that the 4HB and the 3HB signals correspond, respectively to two and one hydrogen atoms.…”
Section: Evidence Of 4hb Incorporation In the Polymer By 1 H Nmrsupporting
confidence: 58%
“…In addition to this, nutrient level in media as compared to C affects the quality of PHA. The study of kinetics of P(3HB:4HB) production by Cupriavidus necator strain A-04 has shown that production of 4HB monomers was high under nitrogen (N) rich medium whereas, 3HB incorporation increases in N-limiting media [73]. Under N-limiting conditions 4HB precursors flux goes to 3HB-CoA, thus more 3HB is incorporated into polymer P(3HB:4HB) by C. necator.…”
Section: Culture Conditionsmentioning
confidence: 99%
“…In 1994, they described another bacteria, Comamonas acidovarans which is a wild type microorganism with suitable metabolic pathways for the production of P(3HB-co-4HB) (Saito and Doi 1994). To date, five wild type bacteria, which can produce P(3HB-co-4HB), i.e., R. eutropha, (Nakamura et al 1992;Kim et al 2005;Chanprateep et al 2008), A. latus (Hiramitsu et al 1993;Kang et al 1995), C. acidovorans (Saito and Doi 1994;Lee et al 2004), Comamonas testosteronii (Renner et al 1996) and Hydrogenophaga pseudoflava (Choi et al 1999), have been reported.…”
Section: Introductionmentioning
confidence: 99%